1997
DOI: 10.1007/pl00005107
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian glial cells in culture synthesize acetylcholine

Abstract: In the present study we demonstrate that acetylcholine is synthesized by cultured mammalian glial cells identified by cell-type specific markers. Primary cultures of rat brain astrocytes or microglia contained 2.0 and 1.6 pmol acetylcholine/10(6) cells on average respectively. Astrocyte cultures established from neonatal mouse brain contained even more acetylcholine (about 80 pmol acetylcholine/10(6) cells). Primary cultures of rat brain astrocytes showed choline acetyltransferase (ChAT) enzyme activity of 3 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Previous studies from our laboratory and other laboratories have shown that acetylcholine and M3 receptors are expressed in a wide variety of normal endothelial and epithelial cell types (5)(6)(7)(8)(9)(10)(11)(12)(13). This suggests that cancers derived from these diverse cell types will similarly coexpress acetylcholine and M3 receptors.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous studies from our laboratory and other laboratories have shown that acetylcholine and M3 receptors are expressed in a wide variety of normal endothelial and epithelial cell types (5)(6)(7)(8)(9)(10)(11)(12)(13). This suggests that cancers derived from these diverse cell types will similarly coexpress acetylcholine and M3 receptors.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, it has been established that acetylcholine is also widely synthesized by a variety of nonneuronal cell types, including keratinocytes (5), airway epithelial cells (6,7), glia (8), vascular endothelium (9, 10), placental trophoblasts (11), and ovarian follicular cells (12) among others (13). Expression of acetylcholine has been unambiguously shown in these cells and tissues as shown by the presence of choline acetyltransferase, the enzyme that synthesizes acetylcholine, and by demonstration of acetylcholine synthesis in these cells as measured by high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes cultured from neonatal mouse brain, contain significant levels of ACh (about 80 pmol/10 6 cells) as well as activity of ChAT, suggesting the endogenous production of ACh in these cells (Wessler et al, 1997). In addition, a recent report indicates that synaptically released ACh in hippocampal slices can activate muscarinic receptors on astrocytes (Araque et al, 2002).…”
Section: Possible Sources Of Ach For Nachr Activation In Nonexcitablementioning
confidence: 99%
“…The recent discovery that lung cancers synthesize and secrete acetylcholine (ACh) that acts as an autoparacrine growth factor provides potential new targets to inhibit lung cancer growth. 3,4 It is well established that ACh is an important neurotransmitter in the central and peripheral nervous systems and acts via activation of ACh receptors (AChRs).Recently, it has been found that ACh is also widely synthesized by a variety of non-neuronal cell types including airway epithelial cells, 5,6 keratinocytes, 7 small and large intestine, gall bladder, 8 glial, 9 vascular endothelial, 10 immune cells and most common cancer cells such as NSCLC, SCLC, colon, glial and ovarian carcinomas. [11][12][13][14][15][16] Although the primary function has not yet been completely elucidated, the expression of ACh in many different cell types suggests that its roles will be fundamental and will present novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%